(untitled) (Research, Society and Development, 2020)
The few fluviometric information related to the temporal-space inconsistency of available historical data, has resulted in great restriction to represent the dynamics of water resources in hydrological studies, mainly of flows. An alternative widely used in hydrographic basin researches is the application of regionalization of flows that determines their water availability, through flow data. In this case, this work had as main objective to regionalize the maximum flows associated with 10-year return periods, long-term and minimum averages with 7 days duration and 10-year return period in the Itapicuru River Basin, in the State of Bahia. Hydrological physico-climatic and relief information was used as the input database. Through the clustering methodology, this work determined three homogeneous regions of the hydrographic basin based on the explanatory variables: precipitation, evapotranspiration, precipitation-evapotranspiration ratio, area and NDVI. All variables showed interaction in at least one adjusted model, except for the explanatory variable NDVI, which was less expressive in the development of the proposed flow regionalization models, not showing a relevant impact in relation to the performance of the other variables. The product of this work is a useful tool in the execution of services such as the granting of the right to use water and it should be remembered that if there is necessary to know the value of the flow in places where there are already fluviometric stations used in determining of homogeneous regions, their values ​​will be more accurate than the generated equations themselves.